CIVIL AGENDA IN RUSSIA AND THE POLITICAL REGIME RESTRICTIONS (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2020)
The article considers the political «weight» of the civil agenda, i.e. political alternativesto the domestic political course in modernRussia. Based on the expert survey data and secondary information, the author showsthe changes in the current political agenda in 2019.Agenda was framed by the constitutional reform announcing in 2020. It was a responseto the expectations of changes among Russian people. From the other hand that was anattempt by the government to “catch the agenda” blocking the non-systemic opposition. Thatwas plan to demobilize its supporters by involving them in the discussion about constitutionalamendments
Keywords: civilian alternatives, domestic political agenda, protests, expert survey